Larval morphology and new records of the iconic diving beetle Acilius sinensis Peschet, 1915 (Coleoptera: Dytiscidae: Dytiscinae)—a species well established in western Yunnan, China - Alarie, Yves; Mai, Zuqi; Michat, Mariano C.; Hájek, Jiří (Zootaxa, 2023)
Adults and larvae of the very rare Chinese endemic species Acilius sinensis Peschet, 1915 are newly reported from three localities in western Yunnan, which indicates the presence of viable populations in this area. Based on the available data, the rarity of the species in collections is more caused by collecting bias than actual threat of its habitat loss. All larval instars of A. sinensis are for the first time described according to the now generalized larval descriptive format of Dytiscidae, which incorporates detailed chaetotaxic and morphometric analyses. Like other known Acilius Leach, 1817 larvae, A. sinensis is characterized by the typical Y-shaped median process of prementum. So far as the third instar larva is considered, A. sinensis shares with A. fraternus (Harris, 1828), A. kishii Nakane 1963, A. semisulcatus Aubé, 1838, and A. sulcatus (Linnaeus, 1758) the median process of prementum invaginated at nearly 75% of its length compared to less than 35% in A. abbreviatus Aubé, 1838, A. duvergeri Gobert, 1874, and A. canaliculatus (Nicolai, 1822). As far as chaetotaxy is concerned, A. sinensis is distinguished by the presence of the primary pore PAo located on the ventral face of the parietal. The habitat of the species is briefly commented. Acilius sinensis is here newly proposed for inclusion in the IUCN red list in the category Vulnerable.